PROFIT GROWTH OF BANKING COMPANIES LISTED ON IDX: TOTAL ASSET TURNOVER, RISK PROFILE AND GROSS PROFIT MARGIN - Sasmita, Gita Panji; Gupita Dewi, Nurma; Anta Wibawa, Tio (Akurasi : Jurnal Studi Akuntansi dan Keuangan, 2023)
This study aimed to determine Total Asset Turnover, Risk Profile, and Gross Profit Margin on earnings growth based on contradictory findings from previous studies and fluctuations in banking performance from 2020-2022. This research can provide a more in-depth picture of what influences profit growth, which can serve as a foundation for more effective financial strategies for companies and investors. This study utilizes 51 samples selected by purposive sampling from secondary data of annual reports published on the IDX. Data were analyzed quantitatively using the classical assumption test and multiple linear regression analysis to test the hypothesis. The research results show that TATO has a negative and significant influence on profit growth, and GPM has a positive and significant influence on profit growth. Conversely, the risk profile has a negative and insignificant influence on profit growth. This result shows that the greater the risk profile of banking companies will indicate a decrease in profit growth due to an increase in risk profile, although the influence is not significant. The study implies that bank profit growth is not only caused by banking intermediation, but if banks can maintain credit quality and increase operational efficiency, bank profits will grow.